Evaluation of daylight distribution and space visual quality at medical centers through spatial layout. Issue 5 (3rd September 2021) - Mousavi Asl, Seyede Rahime; Safari, Hossein
ABSTRACT: This research investigates the impact of the layout of the interior spaces, as an independent variable, on the distribution of daylight factor, uniformity rate, drift magnitude, maximum radial line of sight and visual mean depth as dependent variables in medical centers. A quantitative-qualitative research methodology was adopted, including library studies and computer-assisted simulations using Relux software. Also, Depthmap software was utilized to study the indices of space visual quality through Isovist analyses under some scenarios. Results indicated that the appropriate and utilization-oriented layout of interior elements takes a significant part in improving the space visual quality experienced by the users. In this study, an L-type layout with openings oriented toward the light source and vertical partitions along the path through which the daylight got into space was presented as a suitable plan for medical centers as far as optimal and appropriate distribution of daylight within standard ranges were concerned. This layout provided a uniformity rate of 0.5 and a daylight factor close to 5%, with the indicators of space visual quality being more favorable, as compared to the other layouts considered in this study. Graphical Abstract: uf0001